Implementasi Metode Fotogrametri dalam Program Pendaftaran Tanah Sistematis Lengkap (PTSL) di Desa Jorok, Kabupaten Sumbawa - Perdana, Rahmad Rosyadi; Putri, Yolli Eka (SENTRI: Jurnal Riset Ilmiah, 2026)
Complete Systematic Land Registration (PTSL) is a national strategic program intended to accelerate legal certainty over land rights. The Sumbawa Regency Land Office has implemented an Unmanned Aerial Vehicle (UAV)-based photogrammetric method in accordance with Technical Guideline Number 3/Juknis-HK.02/III/2023 to improve the performance of cadastral mapping. This study analyzes the implementation, effectiveness, and efficiency of the photogrammetric method in Jorok Village, Untir Iwes District, and identifies its supporting and inhibiting factors. A qualitative descriptive approach was employed. Data were collected through in-depth interviews, observation, and documentation involving six informants directly engaged in the PTSL process, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that photogrammetry accelerates spatial data acquisition and produces high-resolution orthophotos with reported horizontal accuracy of approximately 2-5 cm when ground control points are properly distributed. Daily mapping productivity increased from about 50-60 parcels using terrestrial surveying to 100 parcels or more using photogrammetry. A village area of approximately 400 hectares could be photographed in seven days and processed within one to two additional days. Nevertheless, only about 60-70% of parcels could be identified directly from orthophotos, while dense vegetation, hilly terrain, weather, and unclear boundary markers required terrestrial verification. Therefore, an integrated photogrammetric-terrestrial approach is the most effective, efficient, and technically accountable model for PTSL implementation in Jorok Village.